An Analysis of an Authentic Casual Conversation and its Implications in Teaching Speaking Skill - Hua, Thi Tin (Publishing House of Economics, 2022)
Both written and spoken language can be used to represent the same experience, however, the way they encode meaning are quite different. It is revealed from the ‘spoken-written language continuum’ introduced by Gerot and Wignell (1994, p. 161) that some spoken genres which are at or near the most-spoken extreme have more typical characteristics of a spoken text than those which are closer to the most-written extreme. Casual conversation - according to Burns, Joyce and Gollin (1996) - is at the most-spoken end of the spoken-written language continuum; therefore, analyzing it would benefit teaching typical characteristics of spoken language. This paper will present an analysis of an authentic casual conversation based on the background theory about characteristic features of spoken texts and afterwards discuss how to apply the results of the analysis to the teaching and learning of speaking skill in the English language classroom.